Becoming a successful entrepreneur / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Entrepreneurship Module for interim students was conducted by the Division of Research, Industrial Linkages, Com-munity and Alumni Networking of UiTM Perak Branch at Seri Iskandar Campus. The same programme had also been conducted earlier at Tapah Campus on February 1, 2018. This entrepreneur-ial module was one of the additional modules designed to ensure the timetable optimisation during the interim session. A total of 236 interim semester students were in-volved in the programme at Seri Iskandar Cam-pus. The briefing of the programme was delivered by Mrs. Izmayani Sa'adin, the Coordinator of the Malaysian Academy of SME and Entrepreneurship Malaysian Academy of SME and Entrepreneurship Development (MASMED) of UiTM Perak Branch.